The Effect of Problem Based Learning Assisted by Quizizz on Students’ Learning Outcomes in Salt Hydrolysis - Ida Ronauli Siburian; Marini Dominik (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
This study aimed to analyze the effect of Quizizz-assisted Problem-Based Learning (PBL) on students’ learning outcomes in salt hydrolysis material. This study employed a true experimental design using a two-group pretest-posttest design. The population consisted of eleventh-grade students of SMA Negeri 10 Medan in the 2025/2026 academic year, comprising six classes. The sample was selected using random sampling, with class XI F-2 as the experimental class and XI F-6 as the control class. The research instrument consisted of 20 multiple-choice questions. The data were analyzed using n-gain and hypothesis testing with a t-test. The results showed that the n-gain values of the experimental and control classes were 0.763 (high category) and 0.511 (medium category), respectively. The hypothesis testing result showed that Sig. < 0.05, indicating that the learning outcomes of students in the experimental class were higher than those in the control class. Therefore, Quizizz-assisted Problem-Based Learning is effective in improving students’ learning outcomes in salt hydrolysis material.